Insidens Dan Faktor Risiko Fibrilasi Atrium Pasca Bedah Pintas Arteri Koroner - Hasril Hadis; Yoga Yuniadi; Idris Idham (The Indonesian Heart Association, 2010)
Background.Atrial fibrillation (AF) is a frequent complication after coronary artery bypass grafting (CABG). It is associated with an increased risk of mortality and morbidity, predisposes patients to a higher risk of stroke, requires additional treatment, and increases the costs of the post-operative care. This study aimed to determine the incidence, timing, and risk factors for AF after CABG in National Cardiovascular Centre Harapan Kita.Methods.We conducted a retrospective cohort study in 138 consecutive patients with sinus rhythm who underwent CABG. The endpoint of study was new onset in hospital AF. Results.AF developed in 36 patients (26,1%). AF occurred 2,67 ± 1,91days (range 0–7 days) after CABG with a peak incidence on postoperative day 2 and 28 patients (77%) had AF within the first 3 day after CABG. Univariate analysis showed that age = 60 years (P<0.001) and number of graft > 3 (P=0.042) were associated with postoperative atrial fibrillation. In multivariate analysis, age = 60 years (P<0.001) RR 6.198 was found to be independent risk factor of AF following CABG.Conclusions.The incidence of post CABG AF is 26.1% and its independent risk factor is age = 60 years.